2003
DOI: 10.1152/ajpendo.00514.2002
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle lipid metabolism with obesity

Abstract: . Skeletal muscle lipid metabolism with obesity. Am J Physiol Endocrinol Metab 284: E741-E747, 2003. First published December 27, 2002 10.1152/ajpendo.00514.2002The objectives of this study were to 1) examine skeletal muscle fatty acid oxidation in individuals with varying degrees of adiposity and 2) determine the relationship between skeletal muscle fatty acid oxidation and the accumulation of long-chain fatty acyl-CoAs. Muscle was obtained from normal-weight [n ϭ 8; body mass index (BMI) 23.8 Ϯ 0.58 kg/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
246
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(275 citation statements)
references
References 41 publications
24
246
1
2
Order By: Relevance
“…It was recently reported that obese subjects are able to maintain normal IMCL stores in the presence of increased lipid oxidation [6]. The previously reported reduced fatty acid uptake and/or fat oxidation in muscle of abdominally obese subjects [1,2,28,29] may be a characteristic of the more obese subject [30], suggesting that IMCL accumulation may only occur in the presence of a reduced capacity to oxidise fat.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was recently reported that obese subjects are able to maintain normal IMCL stores in the presence of increased lipid oxidation [6]. The previously reported reduced fatty acid uptake and/or fat oxidation in muscle of abdominally obese subjects [1,2,28,29] may be a characteristic of the more obese subject [30], suggesting that IMCL accumulation may only occur in the presence of a reduced capacity to oxidise fat.…”
Section: Discussionmentioning
confidence: 98%
“…Based on these results, it can be estimated that with the present number of subjects, a difference in IMCL of at least 25% was required for detection using this method, indicating that we might have failed to identify slight differences between groups. As already indicated above, part of the discrepancy between different studies on obesity and IMCL accumulation in muscle may be related to differences in the type of muscle studied (with concomitant variation in lipolytic activity, muscle fibre type and glycolytic and oxidative enzyme capacity) [35], the degree of obesity [30] or body fat distribution [1].…”
Section: Discussionmentioning
confidence: 99%
“…Following weight loss, they had BMIs in the class II obesity range (35-39.9 kg/m 2 ) ( Table 1). Since the metabolic characteristics of primary myotubes from extremely obese participants may differ from those of obese participants [47], the conclusions drawn from this study may be limited to the population studied. Another limitation was the varying duration of the participants' weight stability prior to biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of the measurement of LCACoA in humans are scarce, but a recent study reported increased LCACoA content in skeletal muscle from overweight/obese and extremely obese individuals compared with normal weight subjects [31]. Furthermore, total LCACoA content has been reported to be a better correlate of insulin action than measurements of TG m [8].…”
Section: Discussionmentioning
confidence: 99%